Antibacterial Compound from Aspergillus elegans SweF9 an Endophytic Fungus from Macroalgae Euchema sp. - Hani Mulyani; Rizna Triana Dewi; Chaidir Chaidir (Indonesian Journal of Pharmacy, 2019)
The antibiotic resistance of bacterial pathogens has become a serious health concern and encouragement to search for novel and efficient antimicrobial metabolites. On the other hand, endophytic fungi have great potential as a natural source for antimicrobial agents. The objective of this study was to isolation antibacterial compound from endophytic fungi of A.elegans SweF9. The fungus was stationarily cultured at 30°C for 12 days in potato malt peptone (PMP) medium, then extracted with ethyl acetate. The antibacterial activities of the extract were evaluated by agar well diffusion method against Gram-poitive (Bacillus subtilis and  Staphylococcus aureus) and Gram-negative (Escherichia coli) bacterial strains. The broth extract was able to inhibit the growth of E. coli, S. aureus and B. subtilis with antibacterial activity index compared to streptomycin sulfate were 84.6%, 91.6%, and 90% respectively. The active compound (1) was purified to yield amorphous white and identified using FTIR, NMR, and EI-MS analyses, revealed identified as (+) - epi-Epoformin. The compound showed an antibacterial activity index of E. coli, S. aureus and B. subtilis  bacterial were 38%, 45%, and 47%, respectively.  Based on these results endophytic fungi A. elegans SweF9 can be used as a new source of potential antibacterial compounds